High temperature tests on partially encased beams - Piloto, P.A.G. (2012)
Partially encased beams (PEB) are composite steel and concrete elements that present several advantages with respect to steel bare elements. This paper presents a set of experimental tests developed using two different beam lengths and two different shear conditions between stirrups and web (W – welded and NW – not welded), at high temperature (200, 400, 600 ºC) and room temperature. The composite section was built-up with IPE100 steel profile and reinforced concrete between flanges. The deformed shape mode and the bending resistance were compared for different temperature levels and stirrup shear conditions (W and NW). The behaviour of PEB was also compared with bare steel at room temperature. Most of the beams attained the ultimate limit state by lateral torsional buckling (LTB), with exception for those tested at 600 ºC, which collapsed by the formation of a plastic hinge (PH).